Handbook of research on biomimetics and biomedical robotics - Habib, Maki K., 1955- (Engineering Science Reference, 2018)
"This book provides broad knowledge in both the theoretical and the practical skills of robotics and mechatronics interdisciplinary field, integrates fundamental and advanced applied knowledge with latest research development to help solving complex interdisciplinary problems, and enables researchers in the field to meet advanced research and prepare them for high level performance recognized around the globe"--